MUSEUM GEDONG KIRTYA SEBAGAI OBJEK WISATA MUSEUM DI KABUPATEN BULELENG - I Nyoman Suka Ardiyasa; Putu Maria Ratih Anggraini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Gedong Kirtya Museum is the oldest lontar museum in Bali which was founded by F.A. Lieffrinck and Dr. H.N. Van der Tuuk in 1928. The purpose of the establishment of Gedong Kirtya was to revive aspects of ancient Balinese culture and Balinese culture that are still alive (survival) by studying and excavating the widest possible range of lontar in Bali and Lombok. The Gedong Kirtya Lontar Museum is managed by the Buleleng Culture Service through the UPT Gedong Kirtya which specifically collects lontar, copies of lontar, books translated from these lontars, as well as a collection of books researched on Balinese culture compiled in the colonial era (colonial era). . The number of manuscripts (lontar and lontar copies) at the Gedong Kirtya Museum to date is more than 5,200 manuscripts, about Balinese history, literature, magic, medicine and so on. Because Gedong Kirtya is a tourist attraction, every visitor is charged an entrance ticket, the amount of which is adjusted to the background of the visitor. Gedong Kirtya has also been designated as a Cultural Property because Gedong Kirtya was established in 1928. This is in accordance with Law Number 11 of 2010 concerning Cultural Conservation. The law states that cultural heritage objects must be at least 50 years old.Keyword : Museum Gedong Kirtya, Wisata Museum